Play me! S A style! Utilising Gadamer to investigate the state of play in South Africa and the potential of play within the CAPS curriculum: two school-based case studies - Cammay, Stafford Raisley (My University, 2015)
This research report examines the state of play in contemporary South Africa utilising Gadamer's concepts of the 'seriousness of play' and the 'relation between play, art and truth'. My investigation argues a more robust approach to Gadamer's thinking; that the investigation of play as it occurs within a particular historical moment in a specific social setting requires a more politicized understanding of the phenomena. [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Humanities, Department of Dramatic Art, University of the Witwatersrand, Johannesburg, in partial fulfilment for the requirements of a Masters degree, March 2015
Keywords: Gadamer, Hans-Georg--1900-2002; Play (Philosophy); Education--Curricula; Education--Philosophy; Ethics